The civilly liable party in criminal proceedings - Tello, Isabel (2025)
The author concludes that the recognition of the “civilly liable party”, invoked by Peruvian criminal jurisprudence in recent years, as a procedural party in Peruvian criminal proceedings, is derived from the provisions of article 111 of the Code of Criminal Procedure.And she argues that it is important to differentiate the civilly liable party from the civilly liable third party, since it is frequent that in the criminal proceedings these institutions are confused; supporting, for example, the incorporation and liability of the civilly liable party with the rules that govern the civilly liable third party, despite the fact that they are institutions with different nature, rules and legal consequences.